The energetic, kinematic and kinetic responses to load carried on the back, on the head and in a doublepack. Issue 9 (2nd September 2021) - Hudson, Sean; Vanwanseele, Benedicte; Barwood, Martin; Low, Chris; Cooke, Carlton; Lloyd, Ray
Abstract: The determinants of energy saving phenomena reported for load carried on the head, back and in a doublepack remain unclear. This study compared the energetic, kinematic and kinetic responses to head (H), back (B) and doublepack (DP) loading. Fifteen volunteers walked on an instrumented treadmill at 3 km . h −1 with 0, 3, 12 and 20 kg in each loading method. Whole body motion, ground reaction forces (GRF) and metabolic cost were measured. H was less economical than B ( p = 0.014) and DP ( p = 0.010). H was also associated with increased step length ( p = 0.045), decreased cadence ( p = 0.001), greater trunk ( p < 0.001) and hip ( p < 0.001) extension and greater minimum vertical GRF ( p = 0.001) than B and DP. In conclusion, no energy saving was found for head- or back-loading but economy may be improved with methods that cause smaller perturbations from unloaded walking. Practitioner summary: Energy saving phenomena have been reported for load carried on the head, back and in a doublepack, yet the determinants are unclear. This study shows that smaller perturbations from unloaded to loaded walking are associated with improved economy for certain load carriage conditions, such as the doublepack.